A Dual-band Compact Microstrip Patch Antenna for 403.5 MHz and 2.45 GHz On-body Communications - Pichitpong Soontornpipit (2018)
© 2016 The Authors. In this paper, a dual-band microstrip patch antenna (MPA) is designed as the wireless body-area networks (WBANs) sensor. The antenna working at 403.5 MHz and 2.45 GHz, located in the medical implant communication services (MICS) band and the industrial, scientific and medical (ISM) band, is presented and studied. The upper chest, a commonly implanted location within a realistic on-body environment, is selected to evaluate the antenna performance using the finite-difference time-domain (FDTD) and the genetic algorithm (GA) methods. Antenna characteristics such as the return loss are analyzed. Comparative results of simulations and measurements are presented.